Early Stressful Life Events, which Caused Depression Probably are Associated with the Development of Dementia - Andrzej, Brodziak; Alicja, Różyk Myrta; Estera, Kołat (Journal of Behavior Therapy And Mental Health, 2016)
Recently the results of a large, prospective population study, important for the diagnosis and treatment of dementia were presented 1. The authors emphasize their conclusion already in the title of the paper and state “Stressful life events are not associated with the development of dementia”. They discuss many studies, which lead to an opposing conclusion, namely that there is the causal relationship between stressful, adverse life  events and the risk of dementia, however they  quote also two other papers leading to a denial of such a relationship.
Keywords: dementia